Perhitungan Perkerasan Lentur Berdasarkan Metode Manual Desai Perkerasan (MDP) (Studi Kasus: Bts. Provinsi Jambi – Peninggalan) - Sartika Nisumanti (Jurnal Tekno Global, 2019)
ABSTRACTRoad section in border area of Jambi Province - Peninggalan is Lintas Timur Sumatera street which link between provinces. So, this road is often crossed by large vehicles with heavy load and increasing traffic volume which affect on these road. Besides the relatively high volume of traffic, a vehicle load which exceeds the permitted limit causing damage to this road section.This is a problem for road user if it isnʼt immediately repaired, therefore itʼs necessary to calculate the planning of flexible pavement thickness for handling and increasing the road.This research is conducted by using secondary data from the IRMS survey method. Deflection data which carried by Falling Weight Deflectomer (FWD) from P2JN in South Sumatera Province. Furthermore, planning of pavement layer thickness by analyzing the average daily traffic (LHR) to obtain the Cummulative Equivalent Standard Axle Load (CESA) value, the age of plan is calculated for 20 years by using the road damage factor (VDF) Manual Design, determining the thickness of the added layer (overlay).Based on the result of analysis with the 2013 Road Pavement Design Manual method, the CESA4 value of 20 years is 178.213.146,32 and the CESA5 value is 569.466.311,89 , while the planned deflection value is 0,285 mm, thickness of added layer (Ho) is 5,197 cm, the correction value of thickness added layer (Fo) is 1,01563 , the thickness of corrected added layer (Ht) is 5 cm. So, the AC-WC overlay is 4 cm. The calculation result of pavement thickness design based on both design chart 3 and design chart 3A if used HRS or CTB is difficult to implement, so the proposed pavement thickness is 3A flexible pavement with AC-WC thickness is 4 cm, AC-BC 6 cm, AC base 24,5 cm, LPA Class A 30 cm.Keywords : 2013 Pavement Design Manual, Flexible Pavement Layer, Thickness of added layer.ABSTRAKRuas jalan  Bts. Prov. Jambi – Peninggalan  merupakan jalan Lintas Timur Sumatera penghubung antar Provinsi. Sehingga ruas jalan ini sering dilintasi oleh kendaraan besar bermuatan berat dan meningkatnya volume lalu lintas yang berpengaruh terhadap penurunan kualitas perkerasan pada ruas jalan tersebut.  Selain volume lalu lintas relatif tinggi, beban kendaraan  melebihi batas yang diizinkann sehingga ruas jalan ini sering terjadi kerusakan. Hal ini menjadi masalah bagi pengguna jalan jika tidak segera diperbaiki, untuk itu perlu dilakukan perhitungan perencanaan tebal perkerasan lentur untuk penanganan maupun peningkatan jalan pada ruas jalan tersebut. Penelitian ini dilakukan dengan menggunakan data sekunder cara survey IRMS, data lendutan  dilakukan dengan alat Falling Weight Deflectomer (FWD) dari P2JN Provinsi Sumatera Selatan.  Selanjutnya perencanaan tebal lapisan perkerasan dengan cara menganalisa lalu lintas harian rata-rata (LHR) untuk mendapatkan nilai Cummulatif Equivalent Standar Axle Load (CESA), Umur Rencana dihitung setiap tahun selama 20 tahun menggunakan Faktor Perusak Jalan (VDF) Manual Design, penentuan tebal  lapis tambah (Overlay). Berdasarkan hasil analisis dengan metode Manual Desain Perkerasan jalan tahun 2013 diperoleh  nilai CESA4 20 tahun sebesar 178.213.146,32 dan nilai CESA5 adalah 569.466.311,89, sedangkan nilai lendutan rencana/ijin adalah 0,285 mm, tebal lapis tambah (Ho) 5,197 cm, nilai koreksi tebal lapis tambah (Fo) 1,01563, sehingga tebal lapis tambah terkoreksi (Ht) 5 cm, jadi nilai lapis tambah  (overlay) Ac-Wc sebesar 4 cm. Hasil perhitungan desain tebal perkerasan berdasarkan kedua bagan desain 3 dan bagan desain 3A menunjukkan bahwa bagan desain 3 jika digunakan HRS atau CTB sulit untuk diimplementasikan, sehingga  tebal perkerasan yang diusulkan adalah perkerasan lentur bagan 3A dengan tebal Ac-Wc 4 cm, Ac-Bc 6 cm, Ac-Base 24,5 cm, LPA kelas A 30 cm. Kata kunci : Manual Desain Perkerasan 2013, lapis perkerasan lentur, tebal lapis tambah